‘Al Qaeda is on our side’: how Obama/Biden team empowered terrorist networks in Syria | MR Online (2022)
Hours after the Feb. 3 U.S. military raid in northern Syria that left the leader of ISIS and multiple family members dead, President Biden delivered a triumphant White House address.